Cities in relations : trajectories of urban development in Hanoi and Ouagadougou - Söderström, Ola (Studies in urban and social change., 2014)
Cities in Relations advances a novel way of thinking about urban transformation by focusing on transnational relations in the least developed countries. Examines the last 20 years of urban development in Hanoi, Vietnam, and in Ouagadougou, Burkina FasoConsiders the ways in which a city's relationships with other places influences its urban developmentProvides fresh ideas for comparative urban studies that move beyond discussions of economic and policy factorsOffers a clear and concise narrative accompanied by more than 45 photos and maps</ul.